Addressing the public health challenge of birth defects in India - Khurmi, Manpreet Singh; Gupta, Medhavi; Chaudhari, Gaurav (Indian Journal of Child Health, 2014)
Birth defects consisted of a group of diverse clinical conditions categorized on the basis of a congenital presentation and a partly or wholly genetic etiology. Although individually rare, birth defects affect 2-3% of all births in India. As India has the largest global annual births, in absolute numbers, India may harbor the largest number of affected children worldwide. There is a need of strategic research and interventions to bring down the rate of birth defects and associated economic burden and also a need to actively screen and identifythem at early stage so necessary intervention (medical or surgical) could be initiated so as to reduce lifelong disability as a result of such defects. The recent child health screening and early intervention service initiative by the Government of India, the Rashtriya Bal Swasthya Karyakram under the National Health Mission is the first attempt in the direction toward providing services for some of the more prevalent birth defects and has the potential to alleviate suffering of affected children especially from rural areas. The data collected from this program could help policy makers to allocate sufficient funds aimed at treatment of birth defects and also develop behavior change communication strategies for prevention of the same.